Heard Island Field Camp and Refuge Locations 2003/04 - HARRIS, URSULA (hasPrincipalInvestigator); SMITH, DAVID T. (processor); Australian Antarctic Data Centre (publisher)
This dataset includes the proposed field camp locations for the 2003/04 science expedition to Heard Island, the locations of the camp sites that were used during the expedition and the locations of some of the refuges on the island that were surveyed during the expedition. It is a point dataset stored in the Geographical Information System (GIS). The proposed field camp locations are shown in a map (refer to link below).